Climate Change Adaptation for Smallholder Farmers in Southeast Asia - Lasco, Rodel; Habito CMD; Delfino, R.J.P.; Pulhin FB; Concepcion RN (World Agroforestry Centre, 2011)
Climate change, defined as any change in the average daily weather pattern over an extended period of time (typically decades or longer) whether due to natural variability or as a result of human activity (Easterling et al. 2007, IPCC 2007a), is happening now, and is already affecting many natural systems around the world (IPCC 2007a). The Intergovernmental Panel on Climate Change (IPCC) declared in its Fourth Assessment Report (AR4) that climate change is unequivocal (IPCC 2007a), evidenced by observed changes in several global and regional climatic indicators. The Food and Agriculture Organizati on (FAO) expects that considerable efforts would be required to prepare developing countries to deal with climate-related impacts, parti cularly in agriculture (FAO 2007). However, the IPCC also notes that recent studies show a high confidence that there are viable adaptation options that can be implemented at low cost and/or with high benefit-cost ratios (IPCC 2007a).